Performance Evaluation of Rain Attenuation Models in a Tropical Station - Abayomi Isiaka Yussuff; Nor Hisham Bin Haji Khamis; Azli Yahya (Institute of Advanced Engineering and Science, 2014)
The non-uniformity of rainfall in both the horizontal and vertical directions makes the estimation of slant path attenuation complex. At frequencies above 10 GHz, the effects of attenuation and noise induced by rain are quite significant. One year satellite attenuation data were sourced from Malaysia East Asia Satellite at Ku frequency band; using ASTRO beacon signals to monitor and measure the slant path rain rate and attenuation at Universiti Teknologi Malaysia, Skudai. Four years’ one minute rain rate ground data at 0.01% of time exceeded were collected using rain gauge. The attenuation exceeded for other percentages of the time was obtained using statistical methods. Different rain attenuation prediction models were investigated and their performances compared. The validation results clearly suggested that the Breakpoint attenuation prediction model produced better results when compared with other models of interest.DOI:http://dx.doi.org/10.11591/ijece.v4i5.6583